Effectiveness of the Independent Farmer Card Program and its Impact on Farmer Welfare - Rokhman, Arif; Muhaimin, A. Wahib; Maulidah, Silvana (Agro Bali : Agricultural Journal, 2024)
Every policy program that is made needs to be evaluated in order to know its successes and shortcomings, one of which can be done by measuring its effectiveness. This study was conducted to analyze the effectiveness of the independent farmer card and its effect on improving farmers' welfare. It is a study that uses a quantitative approach. The sample was selected using random sampling using the Slovin formula so that 100 respondents were obtained. Data analysis was conducted using Structural Equation Modeling-Partial Least Square (SEM-PLS). The results showed that the effect of the CIPP Model on the effectiveness of the Independent Farmer Card Program (KPM) in Bojonegoro Regency showed positive results. Factors such as monitoring, objectives, socialization, and targeting accuracy of the program contribute to its effectiveness. In addition, improvements in each component of the CIPP Model (Context, Input, Process, Product) were shown to increase the program's effectiveness, which also significantly impacted the welfare of farmers in the area.